INTENSITY OF SOCIAL MEDIA USE AND LITERACY SKILLS IN STUDENTS: A STUDY IN THE CONTEXT OF LEARNING, ENTERTAINMENT, AND COMMUNICATION - Saiful Fallah; Ilham; Hartono; Udi Utomo; Syahrul Syah Sinaga; Paulus Widjanarko (European Journal of Humanities and Educational Advancements, 2024)
This research investigates the correlation between social media usage intensity and literacy skills among students in learning, entertainment, and communication contexts. The primary objective is to comprehend the impact of students’ interaction with social media on developing their literacy skills. Employing a descriptive quantitative research design, the study involves 397 high school and vocational school students in Indonesia. Social media usage intensity is categorized into three main aspects: learning, entertainment, and communication. The analysis evaluates students’ timeon social media and the predominant platforms used. Literacy skills encompass understanding, evaluating, and utilizing information from social media. Analysis results reveal a significant correlation between the intensity of social media usage for learning and communication and students’ literacy skills. However, the use of social media for entertainment and specificdimensions of social media usage intensity do not significantly impact students’ literacy. The regression model’s lack of heteroskedasticity is verified using the Breusch-Pagan test. This research contributes significantly to understanding the influence of social media on students’ literacy, with implications for the development of more effective educational strategies. Future research should consider expanding the sample and incorporating more diverse age groups, cultures, and regions. Additionally, careful consideration of control variables, employing more valid measurements, and adopting research designs that integrate quantitative and qualitative approaches can enhance the accuracy and depth of findings. The development of tailored interventions to enhance social media usage and support literacy could be a focal point for future research